Pendidikan Karakter Dalam Islam (Kajian Kitab Cempaka Mulia Perhiasan Manusia Karya TGH. M. Shaleh Hambali) - Sayuti, Sadip Indra (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This article examines character education in booksCempaka Mulia Perhisan Manusa TGH essay. Moh. Shaleh Hambali Bengkel (Dato' Bengkel) local cleric from NTB. His life was accompanied by conditions of educational backwardness and poverty among the people of Lombok. This research uses a qualitative descriptive method with typeLibrary Research (Library Study).Writing books in Malay (Arab Pegon)This is the main attraction of this book to study, the period in which this book was written is quite early in the colonial era of Indonesia by the Dutch. At that time many people were illiterate in Latin letters, while many books were written in Malay letters (goon) especially this book by Dato' Bengkel.